A case report of immune-mediated arthritis in a patient with cutaneous melanoma receiving checkpoint inhibition therapy. Issue 10 (March 2020) - Papaxoinis, George; Anastasopoulou, Amalia; Laskari, Katerina; Diamantopoulos, Panagiotis; Benopoulou, Olga; Gogas, Helen
Abstract: Introduction: Immune checkpoint inhibitors (ICIs) represent an important advance in the treatment of melanoma. ICIs may induce autoimmune phenomena caused by concurrent activation of the immune system against normal cells. During the last years, cases of musculoskeletal side effects, especially immune-mediated arthritis (IA), have been increasingly reported. Patient concerns: We present a 59-year-old woman, who was treated with pembrolizumab for a relapsed BRAF V600E mutated cutaneous malignant melanoma. The patient presented with right knee arthritis on week 30. Diagnosis: The erythrocyte sedimentation rate and serum C-reactive protein levels were elevated, while rheumatoid factor and anti-cyclic citrullinated peptide antibodies were negative. Imaging confirmed the presence of fluid mainly in the suprapatellar bursa. Synovial fluid analysis revealed an inflammatory effusion, while other etiologies of inflammatory arthritis were excluded. Interventions: Arthritis improved with an intra-articular injection of 8 mg dexamethasone. Twelve days later the arthritis relapsed in both knees, and although it was resistant to nonsteroidal anti-inflammatory treatment, it improved with systemic steroids. Tapering of methylprednisolone dose was feasible with the coadministration of leflunomide and subsequently hydroxychloroquine. Outcomes: Arthritis resolved and the patient is free of complications and disease activity 20 months after the initiation of the second line systemic treatment. Conclusions: We present an unusual case of IA associated with pembrolizumab treatment. The originality of the current report is based on the late occurrence, the monoarticular initial distribution, and uncommon location of IA at the knee.